Examining the contributions of parents’ daily hassles and parenting approaches to children’s behavior problems during the covid-19 pandemic - ÜNSAL, FATMA ÖZGE (My University, 2023)
The present study was designed to examine the direct and indirect contributions of parenting daily hassles and approaches to children’s externalizing and internalizing behavior problems during the COVID-19 pandemic. The sample for this study was 338 preschool children (53.6% girls, Mage = 56.33 months, SD = 15.14) and their parents in Turkey. Parents reported their daily hassles, parenting approaches, and children’s behavior problems. Findings from the structural equation model showed that higher levels of parenting daily hassles predicted higher levels of externalizing and internalizing behavior problems. In addition, we found an indirect effect of daily hassles on children’s internalizing behaviors via positive parenting. Further, there was an indirect path from parenting daily hassles to children’s externalizing behaviors through the negative parenting approach. Results are discussed in the context of the COVID-19 pandemic.
Keywords: Tıp; Dahili Tıp Bilimleri; Çocuk Sağlığı ve Hastalıkları; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Child Health and Diseases; Health Sciences; Klinik Tıp (MED); Klinik Tıp; PEDİATRİ; Clinical Medicine (MED); CLINICAL MEDICINE; PEDIATRICS; Pediatri, Perinatoloji ve Çocuk Sağlığı; Pediatrics, Perinatology and Child Health; behavior problems; parenting approaches; parenting daily hassles; the COVID-19 pandemic; parenting daily hassles; the COVID-19 pandemic; parenting approaches; behavior problems